Penerapan Model Pembelajaran Problem Based Learning Berbantuan Wordwall pada Pembelajaran Ekonomi untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Gede Werdyan Werdyatmika; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to improve student learning activities and outcomes through the application of the Problem-Based Learning (PBL) model assisted by Wordwall in economics learning at SMA Negeri 1 Banjar. This study is a classroom action research conducted in two cycles with stages of planning, implementation, observation, and reflection. The subjects of the study were 34 students of grade XI 4. Data were collected through observation of learning activities and learning outcome tests, then analyzed descriptively. The results showed an increase in student learning activities from cycle I to cycle II. In cycle I, visual activities were 66.17%, oral activities 70.26%, listening activities 68.13%, and writing activities 69.28%. In cycle II, it increased to 81.37% in visual activities, 86.6% in oral activities, 83.33% in listening activities, and 84.31% in writing activities. The completeness of student learning outcomes also increased from 67.65% in cycle I to 82.35% in cycle II. Thus, the implementation of the PBL model assisted by Wordwall effectively increases student activity and learning outcomes.